NEXUS AMONG FISCAL SPENDING, MONEY INFLATION AND ECONOMIC WELFARE IN NIGERIA - Felix Odunayo Ajayi; Aduralere Opeyemi Oyelade; Gideon Olugbenga Olanrewaju (Journal of Applied Economics in Developing Countries, 2025)
This study investigates the nexus among fiscal spending, money inflation, and economic welfare in Nigeria. The relationship between these macroeconomic variables is a long-standing topic of interest, as fiscal spending, inflationary pressures, and the economic well-being of citizens are intricately linked. Nigeria, as one of Africa's largest economies, faces a complex set of economic challenges that impact the welfare of its citizens. The country has grappled with mounting fiscal spending pressures to address critical development priorities, while simultaneously battling recurring inflation driven by factors such as fiscal deficits, fluctuations in global oil prices, and policy coordination issues. The study employs the Error Correction Model (ECM) to analyze the dynamics among the variables from 1990 to 2022. The findings revealed that fiscal spending has a positive impact on economic welfare, while money inflation exerts a negative effect. The results underscore the importance of balanced and coordinated fiscal and monetary policies to ensure sustainable economic growth and equitable distribution of welfare improvements. The study's recommendations emphasize the need for enhanced fiscal-monetary policy coordination, efficient allocation of public resources, and targeted interventions to mitigate the adverse impacts of inflation on the economic well-being of citizens.